2008
DOI: 10.1007/s10826-008-9245-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining Relationships Between Ethnic Identity, Family Environment, and Psychological Outcomes for African American Adolescents

Abstract: Ethnic identity has been linked to a number of healthy psychological outcomes for African American adolescents. The levels of conflict and cohesion in the family environment have also been found to be predictive of adolescent mental health. This study examined whether the ethnic identity and levels of conflict and cohesion in the family environments were related to adolescents' psychological adjustment. Participants included 61 African American adolescents, ages 10-14 years old, and their parents. Hierarchical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 49 publications
3
29
1
Order By: Relevance
“…A "weak" ethnic identity has been related to a number of maladaptive and "risky" behaviors, including substance misuse (e.g., Schier, Botvin, Diaz, & Ifill-Williams, 1997) and antisocial behaviors (Smith et al, 1999). Street et al (2009) found that weak ethnic identity and poor family cohesion were salient predictors for depressive symptoms in adolescents.…”
Section: Ethnic Identity and Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…A "weak" ethnic identity has been related to a number of maladaptive and "risky" behaviors, including substance misuse (e.g., Schier, Botvin, Diaz, & Ifill-Williams, 1997) and antisocial behaviors (Smith et al, 1999). Street et al (2009) found that weak ethnic identity and poor family cohesion were salient predictors for depressive symptoms in adolescents.…”
Section: Ethnic Identity and Outcomementioning
confidence: 99%
“…The Multigroup Ethnic Identity Measure (MEIM; Phinney, 1992) was developed to assess ethnic identity across diverse groups and is the measure that appears to have been utilized most often by researchers investigating ethnic identity (e.g., Street, Harris-Britt, & Walker-Barnes, 2009;Yasui, Dorham, & Dishion, 2004). The MEIM examines general aspects of ethnic identity, such as sense of belonging, attitudes toward an individual's own group, and self-identification as a member of an ethnic group.…”
mentioning
confidence: 99%
“…A positive and clear ethnic identity can facilitate a sense of freedom, security, and comfort, whereas a negative and ambiguous identity may lead to confusion and ambivalence. The unsuccessful resolution of identity development for adolescents has been associated with a host of negative physical and mental health outcomes [4953]. …”
Section: Introductionmentioning
confidence: 99%
“…Family annual income also can be a predictor variable to Bai ethnic identity exploration. This is supported by Street's study which showed that annual family income was positively correlated with higher ethnic identity and adolescents of higher socioeconomic status reported more positive feelings of being members of their group (Street, 2009).…”
Section: Contextual Factors Influence Bai Ethnic Identity Explorationmentioning
confidence: 69%